An introduction to the healthy corner store intervention model in Canada - Mah, Catherine L. (Can J Public Health, 2017)
SETTING: The majority of Canadians’ food acquisition occurs in retail stores. Retail science has become increasingly sophisticated in demonstrating how consumer environments influence population-level diet quality and health status. The retail food environment literature is new but growing rapidly in Canada, and there is a relative paucity of evidence from intervention research implemented in Canada. INTERVENTION: The healthy cornerstore model is a comprehensive complex population health intervention in small retail stores, intended to transform an existing business model to a health-promoting one through intersectoral collaboration. Healthy corner store interventions typically involve conversions of existing stores with the participation of health, community, and business sector partners, addressing business fundamentals, merchandising, and consumer demand. OUTCOMES: This article introduces pioneering experiences with the healthy corner store intervention in Canada. First, we offer a brief overview of the state of evidence within and outside Canada. Second, we discuss three urban and one rural healthy corner store initiatives, led through partnerships among community food security organizations, public health units, academics, and business partners, in Manitoba, Ontario, and Newfoundland and Labrador. Third, we synthesize the promising practices from these local examples, including aspects of both intervention science (e.g., refinements in measuring the food environment) and community-based practice (e.g., dealing with unhealthy food items and economic impact for the retailer). IMPLICATIONS: This article will synthesize practical experiences with healthy corner stores in Canada. It offers a baseline assessment of promising aspects of this intervention for health and health equity, and identifies opportunities to strengthen both science and practice in this area of retail food environment work.